Transition or transitions? Analyzing the fertility decline in Brazil in the light of educational levels - Adriana de Miranda-Ribeiro; Ricardo Alexandrino Garcia (Revista Latinoamericana de Población, 2013)
In Brazil, the reproductive behavior is differentiated according to educational level. The main objective of this article is to analyze fertility differentials by educational level in order to seek characteristics that determine the particular stage of the demographic transition of each educational group. The study will focus on the analysis of fertility level (TFR), parity composition, mean age of childbearing and tempo effect (BF Model). Data come from the Brazilian Demographic Censuses (1980 to 2010). Brazil seems to be completing the (first) demographic transition: fertility is below the replacement level, the mac is starting to increase and the percentage of higher order births is decreasing. Because of the great social inequality, one can identify groups in distinct stages of the transition. Regarding fertility, highly educated women are facing the sdt, while the lesser educated are facing the FTD.